The Re-Awakening Role of Social Workers in Policy-Making Following a Global Pandemic: Lessons for Education and Practice - Pentaris, Panagiotis (Ревија за социјална политика/Journal of Social Policy, 2024)
Social workers have largely contributed to policy analysis and planning since the rise of the discipline’s professional identity. It is through lobbying, policy advocacy and macro-practice that responses about human rights and social justice are crafted and integrated in international and transnational social work practice. Yet, these roles have for a while been suppressed in an attempt to standardise and confine the profession in the limits of a given nation’s legal and social status. Public crises like the recent novel virus SARS-CoV-2, come to force us to rethink what has been the role of social workers before such crises. Are we well prepared to take on these roles again, when for a long while education and practice has shied away from them, leaving contemporary practitioners in a predicament situation? This paper will explore both challenges and opportunities in social policy, arising from COVID-19, and will argue the need for re-emphasising on the social workers’ role in social policy, with the intention to make recommendations for education and practice.